2018
DOI: 10.1002/2211-5463.12430
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia‐induced epiregulin expression by IL‐6 production in human coronary artery smooth muscle cells

Abstract: Patients with obstructive sleep apnea ( OSA ) experience repetitive episodes of desaturation and resaturation of blood oxygen (known as intermittent hypoxia or IH ), during sleep. We showed previously that IH induced excessive proliferation of rat vascular smooth muscle cells through upregulation of members of the epidermal growth factor family, especially epiregulin ( EREG ), and the erbB2 receptor. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Our in vitro model confirmed that IH increased IL-6 in human coronary artery smooth muscle cells (hCASMCs) [35]. Similarly, increases of IL-6 and IL-8 with IH have been observed in both human endothelial cells and cardiac myocytes [44,67,80].…”
Section: Interleukin (Il)-6supporting
confidence: 78%
See 3 more Smart Citations
“…Our in vitro model confirmed that IH increased IL-6 in human coronary artery smooth muscle cells (hCASMCs) [35]. Similarly, increases of IL-6 and IL-8 with IH have been observed in both human endothelial cells and cardiac myocytes [44,67,80].…”
Section: Interleukin (Il)-6supporting
confidence: 78%
“…On the other hand, our study of RASMCs found that sustained hypoxia (1% O 2 ) induced a large increase of GLUT1 mRNA and IH which led to a very slight increase of GLUT1 mRNA [63]. Furthermore, IH has been shown to significantly increase IL-6 expression, which is mainly mediated by NF-κB rather than HIF-1 [35]. In conjunction with the studies showing the involvement of NF-κB in IH, these results suggest that, in VSMCs, HIF-1 has more difficulty functioning in response to IH, as compared with NF-κB .…”
Section: Reactive Oxygen Species (Ros) and Transcriptional Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The serial dilutions were run to verify the specificity and to test the sensitivity of the SYBR Green-based real-time RT-PCR. The respective mRNA levels were normalized by those of the β-actin mRNA for human, by those of Rig/RpS15 mRNA for mouse mRNAs, and the miR levels were normalized by U6 RNA level as an internal standard [4,20,22,25,26,27,28,29].…”
Section: Methodsmentioning
confidence: 99%